Peran Guru Akidah Akhlak dalam Membiasakan Adab dan Pengamalan Ibadah Amaliyah Peserta Didik Studi Kasus di MA Muhammadiyah Bandar Pacitan - Eni Sukarti (BASICA, 2024)
This study aims to analyze the role of Akidah Akhlak teachers in shaping students’ moral conduct and fostering the practice of religious worship activities at MA Muhammadiyah Bandar Pacitan. The study focuses on three main aspects: (1) the role of Akidah Akhlak teachers in developing students’ manners and character, (2) the role of teachers in habituating students to perform religious worship practices (ibadah amaliyah), and (3) the supporting and inhibiting factors encountered in the implementation process.This research employed a qualitative approach using a case study design. The data were collected through in-depth interviews, participatory observations, and documentation. Furthermore, the data were analyzed using the interactive model of Miles and Huberman, which consists of data reduction, data display, and conclusion drawing and verification.The findings reveal that: (1) Akidah Akhlak teachers play a significant role in fostering students’ manners through exemplary behavior, habituation, advice, supervision, and continuous guidance; (2) in strengthening students’ worship practices, teachers function as educators, motivators, facilitators, and supervisors through various religious activities, including salat dhuha, Qur’anic recitation (tadarus), congregational prayers, voluntary fasting, collective dhikr, and daily prayers; and (3) the supporting factors include teachers’ religious personalities, a conducive religious school environment, and support from school leaders and parents. Meanwhile, the inhibiting factors consist of students’ diverse family backgrounds, the negative influence of social media, limited religious awareness among some students, and insufficient time allocation for religious habituation activities.